2021
DOI: 10.1001/jama.2021.17380
|View full text |Cite
|
Sign up to set email alerts
|

Association of Maternal Antidepressant Prescription During Pregnancy With Standardized Test Scores of Danish School-aged Children

Abstract: Key PointsQuestionIs there an association between maternal antidepressant prescription during pregnancy and standardized test scores of Danish school-aged children?FindingsIn this population-based retrospective cohort study that included 575 369 public schoolchildren in Denmark, maternal antidepressant prescription during pregnancy was associated with significantly lower standardized test scores (range, 1-100) in mathematics (adjusted test score difference, −2.2) but no significant difference in language test … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 33 publications
2
30
0
Order By: Relevance
“…Fifth, potential mediators, such as psychotropic and antiepileptic prescriptions, may be misclassified as covariates. However, here, we used the presence of these prescriptions as proxies for comorbid conditions, as is common in pharmaco‐epidemiological research 44,45 46 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifth, potential mediators, such as psychotropic and antiepileptic prescriptions, may be misclassified as covariates. However, here, we used the presence of these prescriptions as proxies for comorbid conditions, as is common in pharmaco‐epidemiological research 44,45 46 .…”
Section: Discussionmentioning
confidence: 99%
“…However, here, we used the presence of these prescriptions as proxies for comorbid conditions, as is common in pharmaco-epidemiological research. 44,45 Moreover, we may be underestimating the effect of second and third trimester exposure on preterm birth because of immortal time bias, i.e., the error in estimating the association between the exposure and the outcome that results from the exclusion of time intervals. 46 However, it is important to note that 20,259 (94.7%) of children in our study were exposed to antidepressants in the first trimester.…”
Section: Strengths and Limitations Of Studymentioning
confidence: 99%
“…9 10 Even though multiple studies have shown that antidepressants are not major teratogens, [11][12][13][14] findings remain inconsistent about the risk of longer-term neurodevelopmental outcomes in children, for example, attention-deficit/hyperactivity disorders (ADHD), autism spectrum disorder or scholastic skills. 15 16 Current data about the reproductive safety of antipsychotics and benzodiazepines are limited, [17][18][19] while the short-term and longterm risk posed by the antiseizure drug valproate is now well acknowledged. 20 21 In women with a perinatal mental illness, elevated risk perception of adverse outcomes in offspring due to psychotropic medication exposure often affects the decision-making regarding their treatment.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…The intraclass correlation was below 0.05 in all models, indicating that similarity was low within regions. All statistical analyses were conducted using STATA MP V. 16.…”
Section: Association Analysesmentioning
confidence: 99%
“…Scholastic skills are important indicators of cognitive function, but they are infrequently assessed in perinatal pharmacoepidemiologic studies. 14 , 15 , 16 Scholastic skills, including reading and mathematics abilities, depend on cognitive processes related to executive function and working memory. 17 Thus, scholastic skills can estimate future academic achievement, career aptitudes, and socioeconomic status.…”
Section: Introductionmentioning
confidence: 99%